Secure Attachment and Self-Compassion among Adolescents: A Gender-Based Moderation Analysis - Wulantika, W; Munawaroh, Eem (KONSELOR, 2025)
Self-compassion is a significant psychological aspect that plays a crucial role in helping adolescents cope with psychological distress and challenging circumstances. During the adolescent period, individuals tend to have low self-compassion due to frequent rumination and self-evaluation. Secure attachment is one of the psychological factors that could potentially influence the level of self-compassion. Thus, this study aims to analyse the relationship between secure attachment and self-compassion in high school students, considering gender as a moderating variable. The study included 206 Teuku Umar High School students in Semarang, consisting of 106 females and 100 males. Data collection techniques employed the Self-Compassion Scale (26 items) and the Inventory of Parent and Peer (19 items). The results of the analysis revealed a positive relationship between secure attachment and self-compassion, with an R coefficient value of 0.3308 and R² of 10.94%. While secure attachment did not significantly affect overall self-compassion directly (p = 0.4760), gender was found to significantly moderate the relationship (p = 0.0256). These findings suggest that women tend to have higher levels of self-compassion than men. However, high secure attachment in women is associated with lower self-compassion levels. This is due to the complex influence of sociocultural norms on emotional regulation and self-evaluation in women. This research highlights the importance of gender consideration in comprehending the dynamics between secure attachment and self-compassion. The implications of these results point to the need for a more sensitive approach to gender differences in developing self-compassion for adolescents. Future research is urged to explore other factors that influence self-compassion, as well as using a longitudinal design to capture changes in this relationship over time.